Analysis of the Internal Cash Control System at BPJS Ketenagakerjaan Belawan Branch - Yenni Ramadhani Harahap; Yopiza; Iswandi Idris (SEAN Institute, 2022)
A company that has a good internal control system is a company that is able to separate functional responsibilities clearly, has a good authorization system and recording procedure, and has adequate resources. BPJS Employment Belawan Branch Office conducts many cash receipts and disbursements transactions that occur every day, so an internal control system is needed that is able to maintain the integrity of accounting information and protect company assets against fraud and abuse. The importance of the role of the internal cash control system in the company in carrying out its operations so that the company's goals can be achieved is the background of the research. The purpose of the study was to analyze the Internal Cash Control System at BPJS Ketenagakerjaan Belawan Branch. Methods: with the first stage of data collection: Types of data: primary data and secondary data. Data sources: internal data and external data. Data collection methods: filed research, observation and interviews. Stage 2 data analysis: Data Analysis Methods: Collecting data, classifying, interpreting, conclusions. Stage 3 Publication related to the Analysis of the Internal Cash Control System. The Internal Control System for Cash Receipts and Disbursements at BPJS Ketenagakerjaan Belawan Branch has been running well. This can be seen from the documents used, related functions, procedures and records of cash receipts and disbursements, but internal audits by SPI are carried out every 2 years. Every cash receipt and cash disbursement must be authorized by the head of the court so that there is no fraud or misuse. The use of cash receipts and disbursement documents is carried out properly, using documents in all transactions and authorized by the Head of Finance. The occurrence of transactions involving cash must be carried out properly by the Head of the Finance Division. BPJS Ketenagakerjaan Belawan Branch has separated parts/functions according to the authority, duties and responsibilities as well as conducted an objective selection for each new employee in order to obtain reliable and appropriate employees as required by the company.